Morphological and Anatomical Features of Left Anterior Descending Artery Intima-Media Thickness in a Sample of Pakistani Population - Adnan Salim Malik, Arz Muhammad, Touseef, Nida Qasim Hayat, Fatima Qaiser, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A recognized surrogate marker that can be utilised for the prediction and profiling of atherosclerotic cardiovascular disease is the thickness of the intima-media layer. Despite the fact that it varies geographically and ethnically, the significantly less likely to have it documented. This is despite the fact that there are many different communities . As a result of the process of atherosclerosis, the left anterior descending coronary artery is one of the coronary arteries that is afflicted the most of the time. As a consequence of this, the goal of this study was to determine whether or not there is a correlation between the intima-media thickness of the left coronary artery and the characteristics of the artery based on its morphology. Time and Place of study: Shaikh Zayed Hospital Lahore March 2019 to October 2021 Results: The thickness of the intima and media, on average, was 0.334 + 0.05 mm. It was more prevalent in males than in females.0.329+0.01 mm in females, increased with the number of branches of the left coronary artery, starting from 0.329+0.01 mm in males bifurcation to 0.499+ 0.01 mm in pentafurcation; and was also greater in left coronary arteries that were shorter than the average length of the right coronary artery 0.5mm, in addition to those with bifurcation angles greater than 700. Conclusion: The length, bifurcation angle, and terminal branching pattern of the left coronary artery all have an impact on the intima-media thickness of the left anterior descending artery. Additionally, the intima-media thickness of the left anterior descending artery is greater in males than it is in females. It can be deduced from this that the morphological characteristics of the left coronary artery are anatomical factors that contribute to the development of atherosclerosis.Screening for atherosclerosis ought to be done on those who exhibit these characteristics in order to provide early intervention